2013
DOI: 10.2147/rmhp.s49535
|View full text |Cite
|
Sign up to set email alerts
|

A lean case study in an oncological hospital: implementation of a telephone triage system in the emergency service

Abstract: Lean practices and thinking have increased substantially in the last few years. Applications of lean practices to health care are found worldwide. Despite that, new contributions are required because the application of lean thinking to hospitals has a long way to go. Lean practices and thinking do not include, in the literature or practice programs, any references to triage systems in health care units. The common triage systems require physical presence, but there are alternative methods to avoid the need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…The implementation of lean healthcare basically focuses on patient's value and preferences of the services. As shown in the Oncological Portuguese Institute Lisbon, which adopting lean thinking in the use of Telephone Triage System, they acquired 82.3% patient satisfaction regarding telephone care and resolution of the problem (14). Applying lean thinking to develop Triage system can decrease both arrivals to physician start time from 62.2 minutes to 41.9 minutes and also the admission waiting time from 54.76 minutes to 24.45 minutes (15,16).…”
Section: Figure 2 Accumulated Frequency Of Papers Included the Reviewmentioning
confidence: 99%
“…The implementation of lean healthcare basically focuses on patient's value and preferences of the services. As shown in the Oncological Portuguese Institute Lisbon, which adopting lean thinking in the use of Telephone Triage System, they acquired 82.3% patient satisfaction regarding telephone care and resolution of the problem (14). Applying lean thinking to develop Triage system can decrease both arrivals to physician start time from 62.2 minutes to 41.9 minutes and also the admission waiting time from 54.76 minutes to 24.45 minutes (15,16).…”
Section: Figure 2 Accumulated Frequency Of Papers Included the Reviewmentioning
confidence: 99%
“…care and the lean thinking of the Lean model of automotive production was recognized in health by the term Lean Healthcare (SUÁREZ-BARRAZA, SMITH, & DAHLGAARD-PARK, 2012), but in Brazil is a sector that is still developing(SOLIMAN et al 2017).According toDickson et al (2009) showed how to use Lean to improve emergency care in a hospital andCarvalho et al (2013) highlighted the potential of Lean Healthcare to improve the screening process of an oncology hospital.For Mazzocato et al (2010) Lean interventions in the health context triggers four mechanisms of change: Shared understanding of processes; the organization and design for efficiency and effectiveness; increased error detection and awareness of process reliability; and finally, collaboration for systematic problem solving and continuous improvement.…”
mentioning
confidence: 99%
“…Especialmente a partir dos anos 2000, diversas organizações de saúde vêm buscando adaptar os conceitos do Lean à realidade de suas operações, o que na literatura ficou conhecido como Lean healthcare. As recentes publicações de Andreamatteo et al (2015); Holden et al (2015); Al-Balushi et al (2014);Drotz;Poksinska (2014) ;De Carvalho et al (2014);Teich;Faddoul (2013); Rinehart (2013); Burgess; Radnor (2013); Radnor et al (2012) demonstram este fato. O Lean Healthcare é tido como uma abordagem promissora para a solução de problemas que, há muito tempo, o setor vem tentando superar, especialmente em setores de alta complexidade como cirurgia e emergência (CASTALDI et al, 2016).…”
unclassified